Marital Disobedience: An Islamic Social Treatment - Karakira, Musatafa Muhammad (Journal of Islamic Sciences, 2025)
The research aims to define disobedience (nushuz), whether it is specific to the wife or extends to the husband, what are the consequences of that, and to respond to the doubts raised by some modernists. The researcher adopted the deductive and demonstrative approach, the analytical and interpretative approach, and the comparative approach. He divided it into three chapters: Chapter One: The disobedience of one of the spouses and the legal rulings that result from it; Chapter Two: The consequences of that and how to resolve them; Chapter Three: The response to some of the doubts of modernists who contradict the legal rulings. Among the results of this research: that disobedience is not limited to the wife, but extends to the husband, and that just as the disobedience of the wife results in rulings, so do the rebellion of the husband.
Keywords: Marriage; Disobedience; Family; Community; Charity